2012
DOI: 10.1371/journal.pone.0036792
|View full text |Cite
|
Sign up to set email alerts
|

Patient Enrolment into HIV Care and Treatment within 90 Days of HIV Diagnosis in Eight Rwandan Health Facilities: A Review of Facility-Based Registers

Abstract: IntroductionAccess to antiretroviral therapy (ART) has increased greatly in sub-Saharan Africa. However many patients do not enrol timely into HIV care and treatment after HIV diagnosis. We studied enrolment into care and treatment and determinants of non-enrolment in Rwanda.MethodsData were obtained from routine clinic registers from eight health facilities in Rwanda on patients who were diagnosed with HIV at the antenatal care, voluntary counselling-and-testing, outpatient or tuberculosis departments between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
1
22
1
1
Order By: Relevance
“…Under PITC a previous HIV diagnosis and enrolment in care might not be communicated to the HCW. Different research by our group (Kayigamba et al, 2012(Kayigamba et al, , 2014 found that before the introduction of PITC the most common reason for testing was the desire to know one's HIV status, while afterwards this was because one was offered a test. Some patients reported an HIV-negative test after their initial positive test when they were tested at a different facility.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Under PITC a previous HIV diagnosis and enrolment in care might not be communicated to the HCW. Different research by our group (Kayigamba et al, 2012(Kayigamba et al, , 2014 found that before the introduction of PITC the most common reason for testing was the desire to know one's HIV status, while afterwards this was because one was offered a test. Some patients reported an HIV-negative test after their initial positive test when they were tested at a different facility.…”
Section: Discussionmentioning
confidence: 96%
“…The current study was part of a cluster non-randomized controlled trial that investigated the HIV testing uptake and acceptability of introducing a PITC intervention in OPDs of Rwandan HFs (Kayigamba et al, 2012(Kayigamba et al, , 2014. Eight Rwandan HFs were purposefully selected for this trial, ensuring inclusion of urban and rural HFs and sufficient numbers of attendees.…”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…This program also has empirical support for its use among South Africans (Van Zyl et al, 2015). While offering HCT through the mobile medium has assisted with testing uptake, most individuals living with HIV remain without needed medical care because they delay linkage to care (Lawn et al, 2006;Losina et al, 2010;Bassett et al, 2010;Kayigamba, Bakker, Fikse, Mugisha, & Asiimwe, 2012 As the most basic explanation, the health belief model demonstrates that individuals will act to avoid poor health. Individuals must first perceive themselves to be at risk and then discern the possibility for risk high enough that action should be taken to avoid harm.…”
Section: Component Three Of the Standard Of Care: Links To Care Call mentioning
confidence: 99%